2020
DOI: 10.3390/medicina56100540
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Time-Restricted Diet on Sleep and Metabolism in Obese Volunteers

Abstract: Background and objectives: A time-restricted diet is one of the various ways to improve metabolic condition and weight control. However, until now, there have been few pieces of evidence and research to verify the methods and effectiveness of time-restricted diets on metabolic improvement and health promoting. We designed this study to make a healthy diet program and to verify the effectiveness of a time-restricted diet on general health, including sleep and metabolism, in healthy volunteers. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Other work has shown benefits of TRE compared to a control condition for quality of life [ 68 , 69 ]. Uncontrolled studies of TRE have shown no significant decrease in pre- to post-depression scores [ 70 , 71 ], although low depressive symptom levels at baseline might help explain these inconsistent findings.…”
Section: Background On Bipolar Disorder (Bd)mentioning
confidence: 99%
“…Other work has shown benefits of TRE compared to a control condition for quality of life [ 68 , 69 ]. Uncontrolled studies of TRE have shown no significant decrease in pre- to post-depression scores [ 70 , 71 ], although low depressive symptom levels at baseline might help explain these inconsistent findings.…”
Section: Background On Bipolar Disorder (Bd)mentioning
confidence: 99%
“…Time-restricted eating did not affect quality of sleep, as assessed by the Pittsburgh Sleep Quality Index (PSQI) [ 4 , 32 , 33 , 34 , 35 , 36 ]. Considering that the percentage of calories consumed after 20:00 is 19.9% on average [ 4 ], all time-restricted eating studies shifted the end of the eating window to earlier than that of the control condition.…”
Section: Effects Of Time-restricted Eating On Sleep and Its Mechanism...mentioning
confidence: 99%
“…Time-restricted eating entails consuming the major portion of one’s daily calorie intake within a limited window of time, which is considered an effective weight-loss strategy. However, aside from the indirect effect it has on sleep through mitigating obesity, it is also shown to positively affect sleep outcomes [ 47 , 42 ] independent of it causing weight loss and improving cardiometabolic health [ 35 , 43 ].…”
Section: Reviewmentioning
confidence: 99%